Bin packing algorithms for virtual machine placement in cloud computing: a review - Kumaraswamy S; Mydhili K Nair (Institute of Advanced Engineering and Science, 2019)
Cloud computing has become more commercial and familiar. The Cloud data centers havhuge challenges to maintain QoS and keep the Cloud performance high. The placing of virtual machines among physical machines in Cloud is signiﬁcant in optimizing Cloud performance. Bin packing based algorithms are most used concept to achieve virtual machine placement(VMP). This paper presents a rigorous survey and comparisons of the bin packing based VMP methods for the Cloud computing environment. Various methods are discussed and the VM placement factors in each methods are analyzed to understand the advantages and drawbacks of each method. The scope of future research and studies are also highlighted.